Relevance of Multimedia Expertise Competency in Vocational Schools toward the needs of Business/Industrial World - Nur Fakhrunnisaa; Sudji Munadi (Journal of Educational Science and Technology (EST), 2019)
This study aims to determine the relevance of vocational school curriculum with the needs of business/industrial world, based on competency profile in the structure of 2013 curriculum after revision. The method used is a survey with quantitative descriptive approach, and data analysis techniques use descriptive statistics. The findings of the study reveals that there are 13 basic competencies of competency profiles needed by the business/industrial world in printing graphic design subject; in 2D and 3D animation subject, there are 19 basic competencies needed; and on audio and video processing engineering subject, all of the basic competencies as many as 18 items are needed by the business /industrial world. In general, all the basic competencies of those three subjects, in terms of percentage, are in the very relevant category. This means that this 2013 curriculum after revision is truly needed and has been relevant to the world f work needs, so that if it’s applied in vocational schools, competency of the graduates of multimedia expertise competency already able to fulfill the competencies of the business/ industrial world